2022
DOI: 10.3390/jpm12060975
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 and Parkinsonian Syndromes: A Systematic Review

Abstract: Coenzyme Q10 (CoQ10) has an important role as an antioxidant. Being that oxidative stress is one of the mechanisms involved in the pathogenesis of Parkinson’s disease (PD) and other neurodegenerative diseases, several studies addressed the concentrations of CoQ10 in the different tissues of patients with PD and other parkinsonian syndromes (PS), trying to elucidate their value as a marker of these diseases. Other studies addressed the potential therapeutic role of CoQ10 in PD and PS. We underwent a systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Moreover, common variants in the Japanese population (p.Val393Ala and p.Leu25Val) and multiple rare variants have been associated with sporadic cases, particularly with a cerebellar MSA phenotype [27][28][29]. Interestingly, decreased coenzyme Q10 levels have also been observed in various tissues of MSA patients not carrying the p.Val393Ala variant [30]. The exact mechanisms linking MSA and Coenzyme Q10 deficiency must still be clarified.…”
Section: Other Causes Of Primary Coenzyme Q10 Deficiency-related Ataxiamentioning
confidence: 99%
“…Moreover, common variants in the Japanese population (p.Val393Ala and p.Leu25Val) and multiple rare variants have been associated with sporadic cases, particularly with a cerebellar MSA phenotype [27][28][29]. Interestingly, decreased coenzyme Q10 levels have also been observed in various tissues of MSA patients not carrying the p.Val393Ala variant [30]. The exact mechanisms linking MSA and Coenzyme Q10 deficiency must still be clarified.…”
Section: Other Causes Of Primary Coenzyme Q10 Deficiency-related Ataxiamentioning
confidence: 99%
“…Decreased levels of CoQ10 indicate an increased risk of PD associated with oxidative stress [ 34 , 35 ]. Several studies have found that the levels of total and oxidized CoQ10 in the CSF of patients with PD are significantly higher than those of patients without neurological disorders [ 36 , 37 ], nd the percentage of oxidized CoQ10 of the total CoQ10 (%CoQ10) in the CSF of the PD group was significantly higher than that of HC group [ 38 ]. Because of its potent antioxidant activity, CoQ10 can be classified as a potential substance for the treatment of PD [ 34 ].…”
Section: Biomarkers In Body Fluidsmentioning
confidence: 99%
“…Supporting this assertion, consumption of MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine), which increases ROS production and leads to a sustained inflammatory reaction, can induce Parkinsonism [ 23 ]. Comparably, elevated circulating oxidative stress markers (e.g., ferritin, 8-OhdG and nitrite) and decreased antioxidant levels (e.g., catalase, uric acid, glutathione) have been observed in PD [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%